Prevalence and antimicrobial susceptibility of Ureaplasma species and Mycoplasma hominis in Greek female outpatients, 2012–2016. (3rd April 2018) - Maraki, Sofia; Mavromanolaki, Viktoria Eirini; Nioti, Eleni; Stafylaki, Dimitra; Minadakis, George
Abstract : Mycoplasma hominis and Ureaplasma species are opportunistic pathogens associated with urogenital infections, complications during pregnancy and postpartum infections. Appropriate empirical antimicrobial treatment is necessary to achieve an optimal therapeutic outcome. This study evaluated the prevalence and the antimicrobial susceptibility of Mycoplasma hominis and Ureaplasma spp. isolated from 1, 008 endocervical samples of outpatients in Crete, Greece, during a five-year period (2012–2016), using the commercially available Mycoview kit (Zeakon diagnostics, France). Ureaplasma spp. was isolated from 116 patients (11.5%), M. hominis from 6 (0.6%), while coinfection with both mycoplasmas was demonstrated in 17 (1.7%). All Ureaplasma strains were susceptible to josamycin and doxycycline. Doxycycline, minocycline and ofloxacin were the most potent antibiotics against M. hominis. Docycycline was proved the most active and is still the drug of choice for the treatment of genital mycoplasma infections. Local surveillance to monitor changes in antimicrobial susceptibilities is necessary to guide treatment strategies.